Constitutional modernism : architecture and civil society in Cuba, 1933-1959 - Hyde, Timothy (University of Minnesota Press, 2012)
How does architecture make its appearance in civil society? This book pursues this challenging question by exploring architecture, planning, and law as cultural forces. Analysing the complex entanglements between these disciplines in the Cuban Republic, the book reveals how architects joined with other professionals and intellectuals in efforts to establish a stable civil society, from the promulgation of a new Cuban Constitution in 1940 up until the Cuban Revolution, offering a new view of architectural modernism as a political and social instrument.